2017
DOI: 10.14503/thij-16-5859
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia and Ulcerative Colitis Associated with Eosinophilic Myocarditis

Abstract: Reactive eosinophilia is associated with inflammatory bowel disease, but its association with eosinophilic myocarditis is rare. We report a case of a 42-year-old man who presented with hypovolemic shock secondary to diarrhea and recently diagnosed nonischemic cardiomyopathy (left ventricular ejection fraction, 0.29). Laboratory evaluation revealed marked peripheral eosinophilia. Cardiac magnetic resonance imaging showed evidence of subacute-to-chronic myocarditis, and endomyocardial biopsy results were consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…EM associated with Ulcerative Colitis (UC) has previously been described in the literature and is associated with more fulminant forms of myocarditis [4]. Myocarditis related to In iximab use has also been described, due to a hypersensitivity reaction, but this as the cause of myocarditis in this patient is unlikely given the absence of peripheral eosinophilia [5].…”
Section: Discussionmentioning
confidence: 90%
“…EM associated with Ulcerative Colitis (UC) has previously been described in the literature and is associated with more fulminant forms of myocarditis [4]. Myocarditis related to In iximab use has also been described, due to a hypersensitivity reaction, but this as the cause of myocarditis in this patient is unlikely given the absence of peripheral eosinophilia [5].…”
Section: Discussionmentioning
confidence: 90%
“…In the literature, which mainly concerns adults, a higher incidence of myocarditis is noted in patients with ulcerative colitis (UC) than CD [ 11 ]. The pathomechanism of myocarditis in IBD seems to be more complex and not fully understood [ 12 ]. The coexistence of infectious, autoimmune conditions or drug-related complications are considered to be involved in development of miocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…UC is a severe disease with many extra-colonic manifestations, such as skin involvement, rheumatic problems, and ocular complications. The frequency of myocarditis associated with UC has been studied only rarely, but there appears to be a high risk of mortality in these patients (5, 6). The mechanisms of myocarditis associated with UC have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy surrounds whether steroid therapy is always necessary for the treatment of EM (1). In contrast, some reports have shown that the treatment of myocarditis with and without eosinophilia associated with UC is focused and effective for the management of UC, often using steroid therapy and/or immunosuppression therapy along with heart failure therapy (6, 18). Previous reports have also demonstrated that steroid therapy is a frequently used and effective treatment for EM patients with UC (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation